The I That Buys: Narcissists as Consumers - Sedikides, Constantine; Gregg, Aiden P.; Cisek, Sylwia; Hart, Claire M. (Journal of Consumer Psychology, 2007)
Which people are most swayed by self‐image motives and hence most likely to make consumer choices in line with those motives? This article contends that the answer is narcissists—individuals who see themselves, and who want others to see them, as special, superior, and entitled and who are prone to exhibitionism and vanity. This work hypothesizes that narcissists will, to validate their excessively positive self‐views, strive to purchase the high‐prestige products (i.e., expensive, exclusive, new, and flashy). In so doing, they will regulate their own esteem by increasing their apparent status and consequently earning others’ admiration and envy. This article also hypothesizes that narcissists will show greater interest in the symbolic than utilitarian value of products and will exhibit, even controlling for self‐esteem, more pronounced self‐enhancement phenomena such as endowment and self‐signaling effects.